Assessment of endothelial function by flow-mediated dilation of the brachial artery in adolescents with a history of preeclampsia or a normotensive pregnancy - Andrade,Joana Adalgisa Furtado Magalhães (2014)
Objectives: to determine the prevalence of endothelial dysfunction and its association with a history of mild and severe preeclampsia in adolescents. Methods: a cross-sectional study was carried out at the MEAC-UFC with 103 primiparous adolescents postpartum. The assessment of endothelial function was performed by way of flow-mediated dilatation of the brachial artery. Variables (age, body mass index, gestational age at delivery, systolic and diastolic blood pressure and flow-mediated dilation) were compared between groups. p<0.05 was considered to be statistically significant. Results: twenty-four (23.3%) patients had preeclampsia (PE): 11 mild and 13 severe. The overall prevalence of endothelial dysfunction was 23.3% (21.5% of patients with normotensive pregnancies and 29.2% of the PE patients: 18.2% of those with mild PE and 38.5% of those with severe PE). The figures were statistically significant for systolic blood pressure, p=0.007. Conclusions: patients with a history of PE have higher systolic blood pressure than patients with a history of normotensive pregnancy, but did not have more endothelial dysfunction.